Backlight module and display device - KANG BAOHONG; JIANG XINGJIA (2022)
The utility model provides a backlight module and a display device. The backlight module comprises a back plate, a circuit board and a dustproof piece, the back plate is provided with an inner surface and an outer surface which are opposite to each other, and the back plate is further provided with a wiring port penetrating to the outer surface along the inner surface; the circuit board comprises a main board part and an extension part which are connected with each other, the main board part is arranged on the inner surface of the back plate, one end of the extension part penetrates through the wiring port and extends out of the outer surface of the back plate, the dustproof sheet is arranged on the outer surface of the back plate and covers the wiring port, and a first avoiding hole for avoiding the extension part is formed in the surface of the dustproof sheet. According to the technical scheme, the automatic assembling efficiency can be improved. 本申请提供了一种背光模组及显示装置。其中，背光模组包括背板、线路板和防尘片，背板具有相对的内表面和外表面，且背板还开设有